A cross-sectional study to unravel the cryptic epidemiology of bovine tropical theileriosis by comparing four traditional and molecular techniques in water buffaloes - JAISWAL, AMIT KUMAR; SUDAN, VIKRANT; PARASHAR, RAHUL; SHANKER, DAYA (The Indian Journal of Animal Sciences, 2016)
A comparison of 4 techniques, viz. blood smear examination, lymph node examination, PCR on blood and PCR on lymph node aspirate for the accurate and sensitive diagnosis of cryptic cases of BTT in water buffaloes, was made. These tests were laboratory standardized and later validated on 85 field samples of suspected bubaline hosts. Keeping blood smear examination as a gold standard for detecting actual number of confirmed positive cases, PCR on blood was 100% sensitive and 88.6% specific. When blood PCR was kept as standard, the lymph node biopsy and lymph node PCR were 90 and 86.96% sensitive along with 77.33 and 90.32% specific, respectively, in detecting theileriosis from suspected samples. The described PCR-based assay provides a valuable tool to study the epidemiology of BTT in buffaloes and some vital data regarding epidemiology of theileriosis in water buffaloes from semi arid parts of India was generated.